Pengaruh Overtime dan Workload terhadap Turnover Intention dengan Job Stress Sebagai Variabel Mediasi (Studi Empiris Pada Karyawan PT Albasia Sejahtera Mandiri Temanggung) - Aliyza Fatrichia; Mulato Santosa (Universitas Muhammadiyah Magelang, 2022)
This study aims to examine and analyze the effect of overtime, workload, and job stress on employee turnover intention, the effect of overtime and workload on employee job stress, the mediating role of job stress on the effect of overtime. on employee turnover intention, and the mediating role of job stress on the effect of workload on employee turnover intention. The sample used in this study were 172 production employees of PT Albasia Sejahtera Mandiri Temanggung. The sampling method used was purposive sampling. The analytical tool used is multiple linear regression analysis with SPSS 25.0. The results of this study indicate that overtime has a positive and significant effect on employee turnover intention, workload has a positive and significant effect on employee turnover intention, overtime has no effect on employee job stress, workload has a positive and significant effect on employee job stress, job stress has a positive and significant effect on employee turnover. employee turnover intention, job stress does not mediate the effect of overtime on employee turnover intention, and job stress mediates the effect of workload on employee turnover intention.